Sampling and recruiting LGBTQ+ populations in health research: reflections on community consultations about antibiotic resistant STIs. - Chandra, Shiva; Broom, Alex; Haire, Bridget; Ridge, Damien; Broom, Jennifer (Health Sociology Review, 2025)
In this paper, we explore negotiations around sexuality and gender diverse identities together with sexual practices, and the materialities of bodies, as they relate to the sampling and recruitment of LGBTQ+ participants in health social science research. The basis of our research note is a reflection on our experiences of undertaking a study on the social dimensions of antimicrobial resistance (AMR) in the context of sexually transmitted infections (STIs). We aimed to identify tensions and important considerations in the sampling and recruitment of LGBTQ+ populations in health and social science research. Recognising the fluidity and diversity of gender and sexuality, the multiple meanings attached to them, and the proliferation of gender and sexuality identifiers, we argue for the critical importance of reflexivity in curating a sampling frame, which is respectful of LGBTQ+ diversity. This contributes to the growing body of work that reflects on how to develop meaningful and informed approaches to do research with LGBTQ+ populations. We do this by complicating the often-linear presentation of sampling and recruitment processes within scholarly research.